Enhancement of properties of recycled coarse aggregate concrete using bacteria. Issue 1 (2nd January 2016) - Sahoo, Kirti Kanta; Arakha, Manoranjan; Sarkar, Pradip; P, Robin Davis; Jha, Suman
ABSTRACT: Due to rapid construction, necessity for raw materials of concrete, especially coarse aggregate, tends to increase the danger of early exhaustion of the natural resources. An alternative source of raw materials would perhaps delay the advent of this early exhaustion. Recycled coarse aggregate (RCA) plays a great role as an alternative raw material that can replace the natural coarse aggregate (NCA) for concrete. Previous studies show that the properties of RCA concrete are inferior in quality compared to NCA concrete. This article attempts to study the improvement of properties of RCA concrete with the addition of bacteria named as Bacillus subtilis . The experimental investigation was carried out to evaluate the improvement of the compressive strength, capillary water absorption, and drying shrinkage of RCA concrete incorporating bacteria. The compressive strength of RCA concrete is found to be increased by about 20% when the cell concentration of B. subtilis is 10 6  cells/ml. The capillary water absorption as well as drying shrinkage of RCA are reduced when bacteria is incorporated. The improvement of RCA concrete is confirmed to be due to the calcium carbonate precipitation as observed from the microstructure studies carried out on it such as EDX, SEM, and XRD.